MicroRNA Expression in Circulating Leukocytes and Bioinformatic Analysis of Patients With Moyamoya Disease - Kang, Kaijiang; Shen, Yuan; Zhang, Qian; Lu, Jingjing; Ju, Yi; Ji, Ruijun; Li, Na; Wu, Jianwei; Yang, Bo; Lin, Jinxi; Liang, Xianhong; Zhang, Dong; et al. (Frontiers in Genetics, 2022)
Objective: MicroRNAs (miRNAs) in exosomes had been implicated differentially expressed in patient with moyamoya disease (MMD), but the miRNAs expression in circulating leukocytes remains unclear. This study was investigated on the differential expression of miRNAs in peripheral leukocytes between MMD patients and healthy adults, and among patients with subtypes of MMD. Materials and methods: A total of 30 patients with MMD and 10 healthy adults were enrolled in a stroke center from October 2017 to December 2018. The gene microarray was used to detect the differential expression profiles of miRNA in leukocytes between MMD patients and controls, and the differentially expressed miRNAs were verified by the method of real-time PCR. The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) were used to explore the key signaling pathways and possible pathogenesis of MMD. Results: The microarray results showed 12 differentially expressed miRNAs in leukocytes of MMD patients compared with controls (fold change >2.0, p < 0.05 and FDR <0.05), of which 8 miRNAs were upregulated (miRNA-142-5p, miRNA-29b-3p, miRNA-424-5p, MiRNA-582-5p, miRNA-6807-5p, miRNA-142-3p, miRNA-340-5p, miRNA-4270), and 4 miRNAs were downregulated (miRNA-144-3p, miRNA-451a, miRNA-486-5p, miRNA-363-3p). The real-time PCR confirmed seven differentially expressed miRNAs (p < 0.05), of which 4 miRNAs (miRNA-29b-3p, miRNA-142-3p, miRNA-340-5p, miRNA-582-5p) were upregulated, and 3 miRNAs (miRNA-363-3p, miRNA-451a and miRNA-486-5p) were downregulated. Both GO and KEGG analysis suggested that the Wnt signaling pathway may be involved in the pathogenesis of MMD. In addition, miRNAs were also differentially expressed among patients with subtypes of MMD. Conclusion: This study indicated that miRNAs are differentially expressed in peripheral leukocytes between MMD patients and healthy adults, and among patients with subtypes of MMD. The Wnt signaling pathway is probably involved in the pathogenesis of MMD.